The interaction effect between teachers’ welfare and human capital on Performance of Government Aided Primary Schools in Isingiro district, Uganda. - Mujuni, Perez Mbiire Batwine; Mwesigye, Adrian R.; Kazooba, Charles Tushabomwe (European Journal of Human Resource, 2022)
Purpose: This research aimed at establishing the effect of interaction between teachers’ welfare and human capital on performance of government aided primary schools in Isingiro district, Uganda. Methodology: A cross sectional research design and post-positivist paradigm were used to collect data from 118 government aided primary schools in Isingiro district, Uganda where 475 respondents participated in the study. The study used closed-ended questionnaires, interview guide and checklists. The schools to be included were selected using simple random sampling and were considered as unit of analysis while the respondents who included District officials, head teachers, teachers and school management committee members formed the unit of enquiry, these were selected purposively based on the knowledge they had on the subject matter. Each school selected, provided the information from the respondents who in this case were the head teacher, two teachers and a chairperson of school management committee member. The research was guided by the null hypothesis, Ho1: An interaction of teachers’ welfare and human capital has no significant effect on performance of government aided primary schools in Isingiro district, Uganda. Findings: The findings of the study revealed that, there is very significant effect between interacting teachers’ welfare and human capital on performance of government aided primary schools (t-value = 11.940, Sig. = .000) thus rejecting the null hypothesis (Ho1). The results signify that since R- Square = 0.288, this means that interacting/ combining both variables of teachers’ welfare and human capital in the model, will contribute 28.8% of good performance of performance of government aided primary schools in Isingiro district, Uganda. Recommendations: The study recommend the government through the Ministry of Education & Sports to impose the training, provide workshops and give minimum-wage law for government aided primary school teachers. This would possibly cater for teachers’ motivation when given some due care and attention. In addition, the Ministry of Education & Sports should create social benefits for government aided primary school teachers as a means to enhance their wellbeing and motivate them. Moreover, it is also recommended that government aided primary schools’ teachers be given allowances such as rental, medical care and transport which could probably motivate them. Since human capital is important for the improvement of primary schools’ performance, it is advisable that the government should provide free trainings and workshops to school teachers’ so that they can gain skills and knowledge and possibly help them performance better at school
Keywords: Teachers’ welfare; Human capital; Performance; Government aided primary schools; Isingiro district; Uganda